Probing the bureaucratic mind : about Canadian federal executives - Hubbard, Ruth, 1942-; Paquet, Gilles (Ottawa, Canada : University of Ottawa Press, 2022)
"This book explores the thinking of Canadian federal public service senior executives through conversations. The transformation of the environment and of the institutional order has created quite a challenge: maintaining some sort of adequacy between these evolving realities and the frames of reference in use by public sector executives. Complexity is often nothing more than a name for a new order calling for a new frame of reference, and the reluctance to abandon old conceptual frameworks is often responsible for fundamental learning disabilities. Through a series of conversations with Canadian federal senior executives about more and more daunting problems --from coping with an evolving context, to engaging intelligently with a new modus operandi, to trying to nudge and tweak programs in order to correct toxic pathologies, to reframing perceptions and redesigning organizations to meet the new challenges--weaknesses of the capabilities of the Canadian federal executives to respond to current challenges were revealed, and suggestions made about ways to kick start a process of refurbishment of these capabilities."--
Reprint. Originally published: Ottawa, Canada : Invenire, 2014.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on March 07, 2025).
eBooks on EBSCOhost
Keywords: Government executives -- Canada; Government executives -- Canada -- Attitudes; Civil service -- Canada; Critical thinking -- Canada; Problem solving -- Canada; Learning ability; Hauts fonctionnaires -- Canada; Hauts fonctionnaires -- Canada -- Attitudes; Pensée critique -- Canada; Résolution de problème -- Canada; Aptitude à l'apprentissage.; Civil service; Critical thinking; Government executives; Government executives -- Attitudes; Learning ability; Problem solving; Canada